Ask Question
12 June, 09:06

Given ⇒ 2 (x - 4) + 6x = 9x - 10

Step 1 ⇒ 2x - 8 + 6x = 9x - 10

Step 2 ⇒ 2x + 6x - 8 = 9x - 10

Step 3 ⇒ 8x - 8 = 9x - 10

Step 4 ⇒ 8x - 8x - 8 = 9x - 8x - 10

Step 5 ⇒ 0 - 8 = x - 10

Step 6 ⇒ - 8 = x - 10

Step 7 ⇒ - 8 + 10 = x - 10 + 10

Step 8 ⇒ 2 = x + 0

Step 9 ⇒ 2 = x

Which step in solving this equation is justified by Combining Like Terms

+3
Answers (1)
  1. 12 June, 09:15
    0
    step 3

    Step-by-step explanation:

    you combine like terms in step 2, therefore justifying Step 3

    (6x + 2x) = 8x
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “Given ⇒ 2 (x - 4) + 6x = 9x - 10 Step 1 ⇒ 2x - 8 + 6x = 9x - 10 Step 2 ⇒ 2x + 6x - 8 = 9x - 10 Step 3 ⇒ 8x - 8 = 9x - 10 Step 4 ⇒ 8x - 8x - ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers